A tactile handle for cane use monitoring - Trujillo-León, Andrés; Ady, Ragou; Vidal-Verdú, Fernando; Bachta, Wael (IEEE, 2015)
Assistive ambulatory devices are used for gait rehabilitation and assistance. In both cases, their benefit is greater when they are used properly. As for canes, embedded sensors can be used for monitoring purposes. In this paper, a custom tactile handle equipping a cane is described. It is composed of cost-effective commercially available pressure sensors. Experimental results involving 10 subjects show that the developed handle can provide information on the cane orientation as well as on the load applied to it during assisted gait. These data can help monitoring the cane usage and misuses detection.
Keywords: Tecnología de la rehabilitación; Force; Monitoring; Correlation; Force sensors; Shafts; Instruments